METHODOLOGICAL FOUNDATIONS OF CONTEMPORARY ENGLISH LANGUAGE TEACHING (SCIENCE TIME JOURNAL, 2026)
This article examines the particular methodological parameters that influence the effectiveness of teaching English in contemporary educational contexts. The study adopts a mixed-methods approach, combining theoretical analysis with empirical data collected through classroom observations, questionnaires, and language testing. The findings reveal that clearly defined instructional objectives, learner-centered approaches, communicative teaching methods, appropriate material selection, and systematic assessment strategies play a significant role in enhancing learners’ language skills and communicative competence.